The values compass : what 101 countries teach us about purpose, life, and leadership - Rai, Mandeep (New York : Simon & Schuster, 2020)
Every day we make decisions based on what we believe in: values that define the ambitions we set, the choices we make, and the relationships we choose. In The Values Compass, Dr. Mandeep Rai shows how the countries of the world epitomize the power of values, provide an ideal guide to help us understand our own, and teach us important lessons about success. From Moroccan compromise to Armenian survival and American entrepreneurship, The Values Compass shows how we can incorporate the values that animate nations into our own lives--seeing ourselves through the eyes of the world, and shedding new light on the opportunities and challenges that define us. The result is an insightful and readable collection that helps us reflect on the values that matter most, last longest, and have the greatest power to create change.
Keywords: Conduct of life; Values. -- Fears; Social values